Juxtaposing the global citizenship competencies of senior high school and college students: Input for a contextualized learning plan - Salvador-Desnacido, Grace Ann; Pecson, Ryan R. (Indonesian Journal of Education and Pedagogy, 2025)
Education and globalization, as tools empowering learners to think and act globally, are driving forces for producing the competent and humanized citizens that the world needs today. The present study explores the global citizenship competencies of senior high school (SHS) and college students as the baseline for a contextualized learning plan premised on that. The study employs the descriptive survey design of quantitative research, wherein the needed data are gathered through a questionnaire to select students with leadership positions in various student organizations in their respective institutions. The data gathered are analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (Independent Samples t-test). The findings reveal that both SHS and college students show strong agreement in possessing global citizenship competencies across knowledge, skills, values, and attitudes, with college students exhibiting slightly higher levels. College students demonstrate significantly more vital global citizenship competencies in knowledge, values, attitudes, and overall domains than SHS students, while no significant difference is observed in the skills domain. A contextualized learning plan is developed to address the learning needs of SHS and college students, aiming to sustain and enhance their global citizenship competencies in knowledge, values, and attitudes through various tailored activities.